2022
DOI: 10.1111/cch.12993
|View full text |Cite
|
Sign up to set email alerts
|

Parental experiences of having a child with CLN3 disease (juvenile Batten disease) and how these experiences relate to family resilience

Abstract: Background CLN3 disease is a neurodegenerative condition presenting in the first decade of life typically leading to death in the third decade. The earliest symptom is rapidly progressive visual impairment followed by intellectual and motor impairments, epilepsy and behavioural disturbances. There are limited data on how the condition affects the family system or the role of family resilience in paediatric neurodegenerative diseases. Methods Semi‐structured interviews were conducted with eight parents (five mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…Having a child with a C3 condition could make them fall between two stools, and they had to arrange meetings with appropriate personnel to receive, for example, respite care (Davies et al, 2004;Steele, 1999;Ware & Raval, 2007;Wood & Milo, 2001) Being shattered in their perception of fatherhood revealed aspects of anticipatory mourning when fathers grieved over losses associated with the progression of their child's life-limiting condition (Rando, 1988(Rando, , 2000. The anticipatory mourning reactions seem to be consistent with findings in previous studies exploring parents' experiences within PPC (Fisher et al, 2021;Hurley et al, 2021;Krantz et al, 2022;Postavaru et al, 2020;Price et al, 2022). In our review, we found that most fathers felt a heightened feeling of love towards their child, which brings to light Rando's (1988) anticipatory mourning theory of being drawn closer to the dying patient.…”
Section: Striving To Be Acknowledged As a Part Of The Caring Teamsupporting
confidence: 90%
See 2 more Smart Citations
“…Having a child with a C3 condition could make them fall between two stools, and they had to arrange meetings with appropriate personnel to receive, for example, respite care (Davies et al, 2004;Steele, 1999;Ware & Raval, 2007;Wood & Milo, 2001) Being shattered in their perception of fatherhood revealed aspects of anticipatory mourning when fathers grieved over losses associated with the progression of their child's life-limiting condition (Rando, 1988(Rando, , 2000. The anticipatory mourning reactions seem to be consistent with findings in previous studies exploring parents' experiences within PPC (Fisher et al, 2021;Hurley et al, 2021;Krantz et al, 2022;Postavaru et al, 2020;Price et al, 2022). In our review, we found that most fathers felt a heightened feeling of love towards their child, which brings to light Rando's (1988) anticipatory mourning theory of being drawn closer to the dying patient.…”
Section: Striving To Be Acknowledged As a Part Of The Caring Teamsupporting
confidence: 90%
“…child, family-centred care, fathers, hospice and palliative nursing, life-limiting conditions, male, paediatric palliative care, palliative care, parents, qualitative research Siden, 2018). In addition, parents report increased financial costs (Brandt et al, 2022), strain on relationships (Krantz et al, 2022;Postavaru et al, 2020) and various emotions, such as uncertainty, chaos, sadness, loneliness and grief (Bally et al, 2018). It has also been found that parents express grieving throughout the trajectory of their child's disease, especially at the time of diagnosis and when the child progressively loses functions (Fisher et al, 2022;Price et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature lacks specific information about many rare diseases, potentially due to the limited number of available participants or lack of funding, which are often by-products of rarity (Baumbusch et al, 2019;Gómez-Zúñiga et al, 2019;Pelentsov et al, 2016). Parents in our study reported wishing for information that would help set expectations about prognosis and progression, which has also been seen in studies about other rare diseases (Baumbusch et al, 2019;Jacobs et al, 2019;Krantz et al, 2022;Pelentsov et al, 2016;Webster, 2019). On the other hand, the variability of A-T and sparse information available occasionally ameliorated worries about the future.…”
Section: Discussionmentioning
confidence: 81%
“…Though many parents found their role rewarding and fulfilling, they also described how their level of involvement in their children's care resulted in difficulties finding time for social interactions, time alone or times where their mind could relax. This phenomenon has also been described in parents of children with other complex conditions (Collins et al, 2020;Currie & Szabo, 2019b;Krantz et al, 2022;Pelentsov et al, 2016), though A-T being rare, progressive, and life-limiting posed unique challenges to A-T parents' experiences. Suggestions from the literature to alleviate parental responsibilities include having a care coordinator, such as a nurse navigator, available to parents of children with rare diseases (Anderson et al, 2013;Currie & Szabo, 2019a).…”
Section: Discussionmentioning
confidence: 82%